PERSEPSI TERHADAP PERANAN BIROKRASI DAN STRESS KERJA PERAWAT - Irawan, Ferry; Diah Sari, Erita Yuliasesti (Universitas Ahmad Dahlan, 2010)
This study aim is to determine the relationship between perceptions of the role of bureaucracy and work stress on nurses. A total of 106 respondents participated in this study. Subjects in this study were nurses of general hospital in Central Java. The results showed that there was significant negative relationship between perceptions of the role of bureaucracy and work stress. This relationship was shown by the correlation coefficient (rxy) = - 0.317 with p = 0.0001 (p <0.01). Perceptions of the role of bureaucracy contribute effectively to the work stress of 10.1% and 89.9% were contributed by other factors.